Ринок плодово – ягідної продукції: економічна суть, внутрішня будова - Колокольчикова, Ірина Володимирівна; Колокольчикова, Ирина Владимировна; Kolokolchykova, Iryna (My University, 2019)
UK: В статті розглянуто категорія «ринок» та її загальний зміст. Визначено місце ринку плодово – ягідної продукції серед видів сільськогосподарських ринків. Встановлено, що на плоди та ягоди існує постійний попит. Надано визначення ринку плодово – ягідної продукції як економічної категорії, наведено його базові риси. Запропоновано комплексний підхід до будови агрегативного ринку плодів та ягід в цілому та за горизонтальним принципом. Розкрито механізм взаємодії всіх елементів ринку даної класифікації. Визначено напрями проведення подальших досліджень щодо оцінки розвитку даного ринку. EN: The article deals with the category "market" and its general content. The place of the market of fruit and berry products among the types of agricultural markets is determined. It is established that there is a constant demand for fruits and berries. The definition of the market of fruit and berry products as an economic category is given; its basic features are given. The complex approach to the structure of the aggregate market of fruits and berries as a whole and on a horizontal principle is offered. The mechanism of interaction of all elements of the market of this classification is revealed. The directions of further researches on estimation of development of the given market are determined.
Market of fruit and berry products: economic essence, internal structure
Keywords: ринок плодово–ягідної продукції; обмін; потреба; попит; пропозиція; потенційні покупці; бізнес–середовище; market of fruit and berry products; exchange; need; demand; supply; potential buyers; business environment